Use of Defoliant to increase Bt cotton productivity - Sarlach, R S; Pathak, D (Indian Farming, 2017)
Most of the high yielding Bt cotton hybrids mature late in November which results in delayed sowing of succeeding wheat crop. Therefore, to bring earliness in cotton without affecting yield is through defoliation as cotton has indeterminate growth habit. Trash contents from leaves affect the fibre quality. The use of defoliants will not only improve quality of picked cotton by reducing trash content but also help to get good market price along with early vacation of field.